2016
DOI: 10.1371/journal.pone.0158858
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Human Lung Cells to Tobacco Smoke Condensate Inhibits the Nucleotide Excision Repair Pathway

Abstract: Exposure to tobacco smoke is the number one risk factor for lung cancer. Although the DNA damaging properties of tobacco smoke have been well documented, relatively few studies have examined its effect on DNA repair pathways. This is especially true for the nucleotide excision repair (NER) pathway which recognizes and removes many structurally diverse DNA lesions, including those introduced by chemical carcinogens present in tobacco smoke. The aim of the present study was to investigate the effect of tobacco s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 95 publications
3
6
0
Order By: Relevance
“…Our findings suggest that chronic CS exposure itself may be sufficient to suppress DNA repair through decreased XPC expression, possibly through promoter hypermethylation, as has been previously described as modulating XPC expression (30). Decreased XPC expression was previously observed 24 hours after in vitro exposure to CS condensate due to proteasomal degradation (31). This suggests that XPC expression may be altered both early after CS exposure, by post-translational modification, as well as later through transcriptional regulation, leading to decreased DNA damage repair, causing increased pulmonary cell death, altered autophagic function, and development of emphysema.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings suggest that chronic CS exposure itself may be sufficient to suppress DNA repair through decreased XPC expression, possibly through promoter hypermethylation, as has been previously described as modulating XPC expression (30). Decreased XPC expression was previously observed 24 hours after in vitro exposure to CS condensate due to proteasomal degradation (31). This suggests that XPC expression may be altered both early after CS exposure, by post-translational modification, as well as later through transcriptional regulation, leading to decreased DNA damage repair, causing increased pulmonary cell death, altered autophagic function, and development of emphysema.…”
Section: Discussionsupporting
confidence: 76%
“…This supports the studies that extracellular nucleotides and nucleosides are essential signaling molecules in the lung for its stability and constancy [54,55]. Additionally, a composite linkage of surface ectonucleotidases regulates nucleotide and nucleoside levels in alveolar lining fluid [56] whereas adenosine mediates the lung workability via the production of energy [57]. Conversely, the reduction of AMP hydrolysis following treatments with 4% DSMFF suggests high conservation of ATP in the lung [58].…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, we observed that WPSC treatment resulted in increased DNA damage and a subsequent increase in γH2AX and 53BP1, which is consistent with the recent finding of Yoshida et al , indicating that tobacco smoking resulted in the increase in mutational burden of lung cells ( 35 ), and with a known increase in the expression of both γH2Ax and 53BP1 in several cancers including breast, bladder, lung, head and neck ( 36 ). By contrast, cigarette smoke has been shown to induce a decrease in nucleotide excision repair mechanisms, and does induce DNA damage as measured by COMET assay ( 37 , 38 ), which raises the interesting possibility that other factors present in WPS may induce a toxic response independent of DNA damage in these cells.…”
Section: Discussionmentioning
confidence: 99%